2022
DOI: 10.1039/d2ta04882e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine platinum-iridium distorted nanowires as robust catalysts toward bifunctional hydrogen catalysis

Abstract: Robust platinum (Pt)-based nanocatalysts exhibit highlighted hydrogen catalysis activities, while the slow kinetics in alkaline medium is still a crucial problem for fuel cells and water electrolysis. Here, we report...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…DTAC (AR, 98%) was supplied by Sinopharm Chemical Reagent Co. Ltd. (Shanghai, China). All other chemicals used in this work were described in our previous works. , …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…DTAC (AR, 98%) was supplied by Sinopharm Chemical Reagent Co. Ltd. (Shanghai, China). All other chemicals used in this work were described in our previous works. , …”
Section: Methodsmentioning
confidence: 99%
“…All other chemicals used in this work were described in our previous works. 37,47 Preparations of PtNiIn FNWs with Different Compositions. To synthesize Pt 66 Ni 6 In 28 FNWs, 10.0 mg of Pt(acac) 2 , 2.1 mg of Ni(acac) 2 , 27.0 mg of DTAC, 20.0 mg of glucose, and 5 mL of OAm were placed in a glass vial.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9c). Wang et al 102 reported ultrafine Pt-Ir distorted nanowires (Pt-Ir DNWs) as a bifunctional catalyst for water splitting to produce green hydrogen. The electrochemical experiment results showed that the Pt-Ir DNWs catalyst has a smaller R ct value than Pt/C, indicating the fast electron transfer of the Pt-Ir DNWs catalyst.…”
Section: Spatial Dimension Regulationmentioning
confidence: 99%